ChemInform Abstract: Rearrangement in the Synthesis of Annulated Lactams Starting from Benzothiazines. Issue 10 (11th March 2014) - Stalling, Timo; Saak, Wolfgang; Martens, Juergen
Abstract A novel ring contraction of benzothiazine based methoxyamides is developed using an intramolecular AlCl3‐ or TiCl4‐promoted Friedel—Crafts reaction to give tetracyclic lactams.